A New Fixed Switching Frequency Direct Torque Controlled PMSM Drives with Low Ripple in Flux and Torque - Sutikno, Tole; Nik Idris, Nik Rumzi; Jidin, Auzani (Journal of Engineering and Technological Sciences, 2011)
Direct Torque Control (DTC) has gained popularity for development of  advanced  motor  control  due  to  its  simplicity  and  offers  fast  instantaneous torque  and  flux  controls.  However,  the  conventional  DTC  which  is  based  on hysteresis  controller  has  major  drawbacks,  namely  high  torque  ripple  and variable  inverter  switching  frequency.  This  paper  presents  an  improved switching strategy for reducing flux and torque ripples in DTC of PMSM drives; wherein  the  torque  hysteresis  controller  and  the  look-up  table  used  in  the conventional  DTC  are  replaced  with  a  constant  frequency  torque  controller (CFTC)  and  an  optimized  look-up  table,  respectively.  It  can  be  shown  that  a constant switching frequency is established due to the use of the CFTC while the reduction of torque and flux ripples is achieved mainly because of the selection of optimized  voltage  vector (i.e.  with an optimized  look-up  table).  This paper also  will  explain  the  construction  of  DTC  schemes  implemented  using MATLAB-Simulink  blocks.  Simulation  results  were  shown  that  a  significant reduction of flux and torque ripples which is about 90% can be achieved through the proposed DTC scheme.